2020
DOI: 10.1177/1078155220913095
|View full text |Cite
|
Sign up to set email alerts
|

Real-world prevalence of hepatitis B virus reactivation in cancer patients in Taiwan

Abstract: Background Hepatitis B virus carriers who receive systemic cancer chemotherapy have been found to be at a higher risk of hepatitis B virus reactivation. However, lack of standard prophylaxis protocol resulted in life-threatening adverse events. Objective This retrospective study is to investigate prevalence and chemotherapy drug-induced hepatitis B virus reactivation in all types of cancer patients and establish an institutional clinical practice protocol. Methodology: This retrospective cohort study evaluat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 30 publications
(85 reference statements)
1
9
0
Order By: Relevance
“…The studies reported hematologic malignancy (10 studies), [27][28][29][30]34,41,43,45,48,54 solid malignancy (four studies), 31,44,47,50 or a combination of both (15 studies). 26,32,33,[35][36][37][38][39][40]42,46,49,[51][52][53] The studies also included rituximab-containing (seven studies), 27,28,30,34,41,43,54 non-rituximab (four studies), 31,42,44,46 or both regimens (seven studies), 32,33,36,38,40,48,49 and the remaining 11 studies did not specify chemotherapy types. 26,29,34,…”
Section: Study Characteristics and Quality Assessmentmentioning
confidence: 99%
See 4 more Smart Citations
“…The studies reported hematologic malignancy (10 studies), [27][28][29][30]34,41,43,45,48,54 solid malignancy (four studies), 31,44,47,50 or a combination of both (15 studies). 26,32,33,[35][36][37][38][39][40]42,46,49,[51][52][53] The studies also included rituximab-containing (seven studies), 27,28,30,34,41,43,54 non-rituximab (four studies), 31,42,44,46 or both regimens (seven studies), 32,33,36,38,40,48,49 and the remaining 11 studies did not specify chemotherapy types. 26,29,34,…”
Section: Study Characteristics and Quality Assessmentmentioning
confidence: 99%
“…26,32,33,[35][36][37][38][39][40]42,46,49,[51][52][53] The studies also included rituximab-containing (seven studies), 27,28,30,34,41,43,54 non-rituximab (four studies), 31,42,44,46 or both regimens (seven studies), 32,33,36,38,40,48,49 and the remaining 11 studies did not specify chemotherapy types. 26,29,34,37,38,45,47,[50][51][52][53] Nineteen studies 27,28,[32][33][34][35][36]…”
Section: Study Characteristics and Quality Assessmentmentioning
confidence: 99%
See 3 more Smart Citations